KEEFEKTIFAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DAN NUMBER HEAD TOGETHER (NHT) DITINJAU PADA ASPEK PRESTASI DAN MOTIVASI BELAJAR MATEMATIKA SISWA SMA NEGERI 1 PALIBELO BIMA - Mariamah, Mariamah (Universitas Pendidikan Mandalika (UNDIKMA), 2014)
This study aimed to: 1) describe the effectiveness of cooperative learning model of Student Teams Achievement Division (STAD) and Number Head Together (NHT) seen from the students’ learning achievement and motivation in learning mathematics; 2) the compare more effective of the two models seen from the students’ learning achievement and motivation in learning mathematics. This study was a quasi-experimental study. It involved two experimental groups. The research population comprised all Year X students consisting of 5 classes, of SMA Negeri 1 Palibelo Bima. From the population, two classes, class X-1 and class X-2, were randomly established as the research sample. Class X-1 was taught using the STAD cooperative learning model and class X-2 1 was taught using the STAD cooperative learning model. The data collecting instruments consisted of a mathematical achievement test and questionnaires for student’s motivation in mathematics. The instrument was validated for its content and construct, while the reliability was measured using Crombach Alpha formula, and then the Standard Error of Measurement (SEM) was calculated. To test the effectiveness of the mathematics learning through the STAD and NHT cooperative learning model, the one sample t-test was carried out. Then to compare the effectiveness of the two models, the data were analyzed using the T2 hotelling test, and the t-test to find out which of the two models was more effective. The result of the study shows that: 1) cooperative learning model of STAD and cooperative learning model of NHT are effective seen from the achievement and motivation in learning mathematics; 2) there is a difference in the effectiveness of the STAD and NHT cooperative learning models in terms of students’ achievement and motivation in mathematics; and 3) STAD cooperative learning model is not more effective compared with NHT cooperative learning in terms of mathematics learning achievement, while STAD cooperative learning model is more effective compared with NHT cooperative learning in terms of motivation in learning mathematics.